Spatial Analysis of the Relationship between Vegetation Index and Land Surface Temperature in Ternate Island, Indonesia - Heinrich Rakuasa; Vadim V Khromykh; Philia Christi Latue (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
This research focuses on the spatial analysis of the relationship between vegetation index and land surface temperature in Ternate Island, Indonesia, which is becoming increasingly relevant amidst the phenomenon of rapid urbanization. The background of the research shows that land use change has the potential to reduce green open space, contributing to an increase in surface temperature that can trigger the Urban Heat Island (UHI) phenomenon. The methods used include utilizing Landsat 8 OLI/TRIS satellite image data to calculate NDVI and LST values and statistical analysis using Pearson's correlation test and Spearman's rho to identify the relationship between the two. The results showed a significant negative relationship between NDVI and LST, with a Pearson correlation coefficient of -0.613, indicating that areas with better vegetation cover tend to have lower surface temperatures, and non-vegetated areas influence the increase of land surface temperature. The discussion highlights the importance of vegetation in regulating surface temperature through evapotranspiration and shading processes and suggests the need for afforestation strategies to mitigate climate change on Ternate Island